IMPROVING MANAGEMENT FOR LEARNING AL-ISLAM AND KEMUHAMMADIYAHAN IN NONFORMAL DEPARTMENT - Elihami Elihami (JURNAL EDUKASI NONFORMAL, 2019)
Learning of Al- Islam and Kemuhammadiyah in nonformal education takes place in STKIP Muhammadiyah Enrekang. The Quran encourages learning as in Surah 20 that says “Lord! Let my knowledge increase” and in the words of Rasullullah (pbuh) “Seek knowledge as far as China”. All these signify that learning, as a process of development and transformation, takes place with no realm of boundary to impede. The procedures include a survey questionnaire and interview to gather related data of the student’s first semester at STKIP Muhammadiyah Enrekang. The analysis hopes to provide learning management input in Al-Islam and Kemuhammadiyahan that promotes structured and relevant findings for future enhancement, understanding and awareness of adult learning in a local situation resulting from the perception, learning and perhaps changes that may result from the learning process.